Prediction of nodal metastasis based on intraoral sonographic findings of the primary lesion in early-stage tongue cancer. Issue 5 (May 2023) - Kawano, S.; Hattori, T.; Mikami, Y.; Chikui, T.; Kawazu, T.; Sakamoto, T.; Maruse, Y.; Tanaka, S.; Hamada, E.; Hiwatashi, M.; Shiraishi, Y.; Oobu, K.; et al.
Abstract: The aim of this study was to clarify the correlation between imaging findings obtained using intraoral ultrasonography (US) and pathological findings of tongue cancers, and to examine the predictive value of intraoral US findings with respect to occult nodal metastasis. This was a retrospective study based on the medical records of 123 patients with T1–2N0 tongue cancer. The depth of invasion (DOI) on intraoral US was positively correlated with the pathological invasion depth (PID) ( ρ = 0.7080, P < 0.0001). Receiver operating characteristic analyses revealed an optimal DOI cut-off value of 4.1 mm and optimal PID cut-off value of 3.9 mm to detect nodal metastasis. Regarding the margin shape of the primary tumour on intraoral US, the incidence of nodal metastasis was significantly higher for the permeated type than for the pressure type ( P < 0.001) and wedge-shaped type ( P = 0.002). Furthermore, tumours with peritumoural vascularity assessed by power Doppler US had a significantly higher incidence of nodal metastasis than tumours without ( P = 0.003). The sensitivity, specificity, and accuracy of the permeated type to predict nodal metastasis was 53.6%, 95.8%, and 86.2%, respectively. These results suggest that intraoral US findings closely reflect pathological findings and could be useful to predict occult nodal metastasis in patients with early-stage tongue cancer.